2007
DOI: 10.4028/www.scientific.net/msf.566.179
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Blast Attenuation on Weight of Barrier Materials

Abstract: The attenuation effect of barrier materials, which covers an explosive completely, on blast waves was studied. The density of the barrier materials was examined to make the barrier materials light and low in volume. Water gel, small spheres of foam polystyrene, and mixtures of these two materials were used as the barrier materials, and the density of the mixture was varied from 0.12 g•cm-3 to 1.0 g•cm-3 by changing the mixed volume ratio. Natural silica sand was also tested for comparison. A spherical PMMA con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Figure 5 shows the distribution of peak overpressure outside the tube; the origin on the horizontal axis is located at the tube exit, for 130-J and 50-J explosions without water, and for 130-J explosion with water. Lines and symbols denote data of the present simulations and the previous experiments [7], respectively. The peak overpressure decreases as the shock wave moves away from the tube exit.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Figure 5 shows the distribution of peak overpressure outside the tube; the origin on the horizontal axis is located at the tube exit, for 130-J and 50-J explosions without water, and for 130-J explosion with water. Lines and symbols denote data of the present simulations and the previous experiments [7], respectively. The peak overpressure decreases as the shock wave moves away from the tube exit.…”
Section: Resultsmentioning
confidence: 90%
“…This paper models experiments in which explosives are detonated inside a straight tube. [7] Figure 1 shows the calculation target. The square tube is 330 mm long and 30 mm on each side.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors also carried out the experiments to evaluate the blast pressure. In a series of the experiments, the authors found that small amount of water on the floor of its storage chamber mitigated the blast pressure remarkably [5]. The authors have been studied the mitigation mechanism by experiments [6,7] and numerical simulation [8,9].…”
Section: Introductionmentioning
confidence: 99%